Clinical Trials in Asia Pacific Region: An Introduction - Ambade, Mrunal (IJRDO-Journal of Applied Science, 2018)
The historical approach to conduct clinical trials and have served drug companies well for the past thirty years are typically located in US, UK Canada and Western European countries The shrinking pools of treatment populations and increasingly intense competitive environment in the traditional North American and Western European markets have led sponsors to approach APAC Region to conduct cost effective quality research and secure timely enrollment of patients. This article focusses on five the most dynamic countries in APAC region.